Managing nirmatrelvir/ritonavir (Paxlovid) interactions in general practice - Mirowska-Guzel, Dagmara; Niedzielko, Magdalena; Kułakowski, Rafał (Family Medicine & Primary Care Review, 2023)
Nirmatrelvir/ritonavir (Paxlovid) is indicated in patients who are at high risk of progressing to severe COVID-19. Many of these patients are concomitantly prescribed various medications for other indications. Ritonavir has no activity against SARS-CoV-2, but, administered with nirmatrelvir, acts as a pharmacokinetic booster, increasing nirmatrelvir’s efficacy. Ritonavir can simultaneously change other medicines’ plasma levels, affecting their safety and therapeutic effects. Ritonavir’s potential to cause clinically significant interactions is well documented, as it has a long history of being used as a pharmacokinetic enhancer with other antiviral agents. Pharmacokinetic drug-drug interactions (DDIs) are a well-known phenomenon, but data on the clinical impact of Paxlovid DDIs is still insufficient. Ritonavir in the treatment of COVID-19 is only administered for 5 days; therefore, uncertainty exists on how the co-administration of various medicines should be managed. Numerous Paxlovid DDIs can lead to serious adverse drug reactions; therefore, careful analysis of all concomitantly prescribed medicines is essential to ensure treatment safe-ty. This article aims to summarise currently available information on Paxlovid DDIs that may be relevant for general practitioners. It explains the main mechanisms leading to pharmacokinetic interactions and possible options for DDIs management. The authors indicate sources of information that may be helpful to prescribers when weighing the benefits and risks of Paxlovid co-administration with other medicines.